Islamic Study in Indonesia in the Perspective of Intellectual History: An Axiological Criticism - Mana, Rivai (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT: Islam as a religion, in fact, has long been a destination of study, not only by Muslims but also by non-Muslims. The focal points of Islamic studies are also diverse, both from the level of Islam as a faith and Islam as a social system. This study develops very rapidly in the scientific East and West traditions today, and takes shape in the discipline of Islamic studies, namely a scientific frame which examines the doctrine of religion and dialectics, and doctrine synthesis and historical dimension in Islamic societies. Criticism addressed to the study of Islam that develops in Islamic world, including in Indonesia, is too strong normative-theological approach and exclusions of historical sociological approach. Similarly, institutions engaged in Islamic studies such as State Islamic University will be giddy to position itself as an academic institution or proselytizing. This paper finally aims to map the initial problem of Islamic studies in Indonesia in the perspective of intellectual history, and also identifies an agenda that can be done, including research models that need to be developed.Keywords: Islamic studies in Indonesia, intellectual history, historical perspective, and axiological criticism.About the Author: Dr. Rivai Mana is a Senior Lecturer at the Faculty of Education and Teacher Training UVRI (Veteran University of the Republic of Indonesia), Makassar City, South Sulawesi, Indonesia. He can be reached at : rivaimana@yahoo.comHow to cite this article? Mana, Rivai. (2012). âIslamic Study in Indonesia in the Perspective of Intellectual History: An Axiological Criticismâ in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.37-54. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 11, 2012); Revised (September 12, 2012); and Published (October 28, 2012).